Role of Striatum in the Pause and Burst Generation in the Globus Pallidus of 6-OHDA-Treated Rats - Kita, Hitoshi (Frontiers Research Foundation, 2011)
Electrophysiological studies in patients and animal models of Parkinson's disease (PD) often reported increased burst activity of neurons in the basal ganglia. Neurons in the globus pallidus external (GPe) segment in 6-hydroxydopamine (6-OHDA)-treated hemi-parkinsonian rats fire with strong bursts interrupted by pauses. The goal of this study was to evaluate the hypothesis that dopamine (DA)-depletion increases burst firings of striatal (Str) neurons projecting to the GPe and that the increased Str–GPe burst inputs play a significant role in the generation of pauses and bursts in GPe and its projection sites. To evaluate this hypothesis, the unitary activity of Str and GPe was recorded from control and 6-OHDA-treated rats anesthetized with 0.5–1% isoflurane. The occurrence of pauses and bursts in the firings of GPe neurons was significantly higher in 6-OHDA than in normal rats. Muscimol injection into the Str of 6-OHDA rats increased average firing rate and greatly reduced the pauses and bursts in GPe. Recordings from Str revealed that most of the presumed projection neurons in control rats have very low spontaneous activity, and even the occasional neurons that did exhibit spontaneous burst firings did so with an average rate of less than 2 Hz. In DA-depleted Str, neurons having stronger bursts and a higher average firing rate were encountered more frequently. Juxtacellular labeling revealed that most of these neurons were medium spiny neurons projecting only to GPe. Injection of a behaviorally effective dose of methyl-l-DOPA into the Str of 6-OHDA rats significantly increased the average firing rate and decreased the number of pauses of GPe neurons. These data validate the hypothesis that DA-depletion increases burst firings of Str neurons projecting to the GPe and that the increased Str–GPe burst inputs play a significant role in the generation of pauses and bursts in GPe. These results suggest that treatment to reduce burst Str–GPe inhibitory inputs may help to restore some PD disabilities.